Recurring outbreaks of Salmonella Typhimurium phage type 135 associated with the consumption of products containing raw egg in Tasmania - Stephens, Nicola; Coleman, David; Shaw, Kathleen (Communicable Diseases Intelligence, 2008)
Large egg-associated outbreaks of Salmonella Typhimurium 135 (STm135) that were associated with inadequate food safety practices but also linked to a common poultry farm occurred in Tasmania in 2005. A series of public health interventions were implemented to prevent further occurrences but 2 more egg-associated outbreaks in Tasmania in March 2007 and January 2008 led to a further 66 cases of STm135. This report describes these outbreaks and their links to the common source associated with the outbreaks in 2005. Commun Dis Intell 2008;32:466–468.